Efektivitas Permainan Tradisional Congklak terhadap Kemampuan Berhitung Anak di Taman Kanak-kanak Telkom Padang - Andary, Lintang Nawang; Yeni, Indra (Darul Yasin Al Sys, 2025)
This study aims to determine the effectiveness of the traditional game Congklak on the development of children's counting skills at Telkom Padang Kindergarten. This research uses a quantitative approach with the Quasi Experiment method. The population in the study were all Telkom Kindergarten Padang students totalling 167 children. The research sample was taken using Purposive Sampling technique, namely class B1 and class B2 with each consisting of 15 children. Data analysis techniques involve prerequisite tests, and data are processed using a difference test (t-test) with the help of the SPSS 23.0 for Windows application. The results showed that in the experimental class that used the traditional game Congklak, the pre-test mean value was 17.67, while the post-test mean value increased to 23.00. Meanwhile, in the control class that used the Snakes and Ladders game, the pre-test average value was 17.87, while the post-test average value increased to 23.00. Meanwhile, in the control class that used the Snakes and Ladders game, the pre-test average value was 17.87, but the post-test average value only increased to 18.87. The results of the t-test (independent sample test) showed a sig (2-tailed) value of 0.000, which means that there is a significant difference because 0.000 <0.05. In addition, the effect size test results showed a value of d = 1.72, which is included in the strong effect category (d > 1). Thus, the hypothesis in this study, namely Ha is accepted and H0 is rejected, it can be concluded that the traditional game Congklak is effective in improving children's counting skills at Telkom Padang Kindergarten.